posted by .

Define the quotient rule.

  • Calculus -

    If f and g are functions of x

    d/dx(f/g) = (f'g - fg')/g^2

    This is just a variation of the well-loved product rule, where f/g = f * g^-1

    d/dx(f * g^-1) = f'*g^-1 + f*(-1)g^-2 * g'
    = f'/g - fg'/g^2
    = (f'g - fg')/g^2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Calculus

    Let f(x)= 5x ------- x–2 are we supposed to use the quotient rule?
  2. Calculus

    f(x)=5+(6/x)+(7/x^2), find f'(x). I haven't done fractions without using the quotient rule im not so sure this would work with quotient rule what do i do?
  3. Calculus

    How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
  4. calculus

    Find the DERIVATIVE: h(x)= e^3x+2/e^3x-2 (quotient rule)
  5. Calculus

    y= [(x-3)/(x^2+1)]^2 I know that I would use the product rule on the whole equation inside the brackets. But would i also do the quotient rule bc of the division?
  6. Calculus

    y= [(x-3)/(x^2+1)]^2 find the derivative. I know i would start off with the chain rule. but would i then continue on and use the quotient rule next?
  7. calculus

    Differentiate: 1/s+ke^s Do I just use the quotient rule?
  8. Calculus

    Match the rule with the title: ____ 3. d/dx [f(x)/g(x) ]=(g(x) f^' (x)-f(x) g^' (x))/[g(x)]^2 ____ 4. d/dx [f(g(x))]=f^' (g(x))∙g'(x) ____ 5. d/dx [f(x)∙g(x)]= f(x) g^' (x)+g(x) f^' (x) ____ 6.d/dx [x]=1 ____ 7. d/dx [f(x)+g(x)]= …
  9. Calculus

    So, I have a homework question on The Quotient Rule (taking derivitives) and I would like to know if I did it right. Calculate: y=(1/sqrt(x))-(1/(5th root of x^3). My 1st step was to change the sqrt to x^1/2, and the 5th root to x^1/5+^3. …
  10. Calculus

    Quotient Rule: Use the limit definition of the derivative to prove that the quotient rule

More Similar Questions